Implementation of Merdeka Curriculum Using Learning Management System (LMS) - Dharma Gyta Sari Harahap; Salman Alparis Sormin; Hariani Fitrianti; Muh. Rafi’y; Ferry Irawan (PT Inovasi Pratama Internasional, 2023)
The purpose of this article is to examine journals about the implementation of the Merdeka Curriculum using (Learning Manajement System) LMS. This article is discussed qualitatively using a literature study from the perspective of critical discourse analysis by examining several journals that are relevant to the topic. The steps taken are (1) collecting data from relevant journals (2) analyzing reading material from journals and making conclusions from the topic of implementing the Merdeka Curriculum using the (Learning Manajement System) LMS. The results of the study in this article show that the implementation of the Merdeka Curriculum is related to (Learning Manajement System) LMS. Implementation of the Merdeka Curriculum is carried out using interrelated (Learning Manajement System) LMS.